A novel technique to restore access in patients with central venous occlusion using the Surfacer® Inside-Out® Access Catheter System. Issue 5 (September 2020) - Baetens, Tarik R; Rotmans, Joris I; van der Meer, Rutger W; van Rijswijk, Carla SP
Exhausted central venous access is a potentially life-threatening situation for patients dependent on haemodialysis. If standard guidewire recanalisation fails, unconventional venous access or central venous needle recanalisation can be considered but are often associated with higher rates of complications and/or dysfunction. Here, we report about two patients treated successfully with the Surfacer ® Inside-Out ® Access Catheter System (Bluegrass Vascular Technologies, San Antonio, TX, USA) to achieve transmediastinal central venous access.